The representation of woman in "Nobleza Baturra" (Cifesa, 1935) and film adaptation in the case of the remake "Morena Clara" (Cifesa, 1936) - Franco i Giner, Josep (Tropelías: Review of Literary Theory and Comparative Literature, 1999)
The fïrst film we will talk about is from the 1935 and is one of the most representative films from "Cifesa" in its republican age. There was a "silent" version, written and directed by Joaquín Dicenta son and Juan Vila Vilamala from the 1925. lt had such a success that Dicenta himself wrote a theatre version of the film. Supposedly, it is from this text that Florian Rey looks the influence to write the script for the 1935 version of the film. This one was presented to the public the 12th of October, the day of the celebration of "el Pilar" (1) and the "Race", in thirty five cities in Spain, with a tremendous success from public and critics. In 1965, another version of the film was made by .luan de Orduña, protagonist himself in the 1935 one. The subject from Nobleza Baturra, castity, will be the core of our discussion. The second film that we will talk about, Morena Clara from 1936, is the third film that Florian Rey makes wilh the valencian producers "Cifesa". Jt becomes evident the interest that Florian Rey shows for the "white" gypsies (2): in 1943 he will direct Ana María, having also as a protagonist a "white" gypsy, and based as well as Morena Clara, on a play by Antonio Quintero and Pascual Guillén, specialists in "calés" comedies. The "white" then, that we will talk aboul, was fïrst a play, debuted in Madrid em 1935, a "costumbrisla" (3) play, with lots of absurd and humanism, in our opinion, not very well understood. There is another film version, from the 1954, directed by Luis Lucia, where it is still more diffïcult to make credible the film realism that wants to relate "payos" (4) with gypsies, and that we will also lalk aboul. And anothe one, finally, from the forties, from Julián Torremocha, that we will not discuss. Two good exemples of the well cinema making of Florián Rey. (1). El Pilar (Virgen Pilar) from Saragossa, is the "Guardia Civil" virgen. "Guardia Civil" is an especial policie: force that played a very importam role in Franco dictatorial regime. (2). Gìypsies are normally tanned. (3). "Costumbrista" is applied of the literature that tries to picture the life of common people. (4). "Payo" is someone that is not a gypsy.